The Influence of Digital Leadership on Employee Affective Well Being with the mediation of Organizational Citizenship Behavior and Job Satisfaction - Nugroho, Sukmo Hadi; Said, Meldasari; Arifin, Zainal (Journal of Ecohumanism, 2024)
The Digital Era, marked by rapid and significant technological developments, is essential for a leader to achieve good quality performance results by the responsibilities that have been given. The performance results of a company can increase due to the influence of leadership style supported by developments in digital technology. Digital leadership is believed to have a positive impact on employee affective well-being, if employees are satisfied with what their leaders provide, it will influence the progress of the company and feel motivated to work better. This research also expands the literature by examining the mediating influence of Organizational Citizenship Behavior and Job Satisfaction and provides new directions for researchers to study Digital leadership and Employee affective well-being—purposive sampling method. The data collection technique began with distributing an initial questionnaire (pre-test) to 50 respondents with the criteria for respondents being employees who had worked for at least 1 (one) year and worked as staff in the company, then continued with a sample of 160 respondents. The research was carried out quantitatively using the Lisrel SEM (Structural Equation Model) method. The research results show that the Digital leadership variable has a significantly positive relationship with Job satisfaction, Organizational citizenship behavior (OCB), and Employee affective well-being. The variables Job satisfaction and OCB have a significantly positive relationship and are good mediators of digital leadership on employee affective well-being.